Firms' Investment Behaviours in Temperature-Controlled Supply Chain Networks. (20th September 2021) - Zhu, Mengshuai; Chen, Hao; Wang, Ximeng; Wang, Yonghan; Shen, Chen; Zhu, Cong
Abstract : Delivering high-quality food into markets is a vital expectation of modern customers. The significant increase in consumers' awareness of food freshness, nutrition, and safety makes the temperature-controlled supply chain (TCSC) the focus of food logistics safety. However, a large number of Chinese companies are still reluctant to invest in the food supply chain, resulting in a high rate of supply chain logistics loss. This research aims to establish an economic model to explain why these companies do not invest and under what conditions they will do. The results show that high economic investment is the main reason that hinders companies' willingness to build TCSC. Large companies with bigger production are more willing to invest in TCSC than small companies. Besides, larger companies running with high-quality products could get more profit while small companies operating with normal products are less competitive.